Implementasi Kebijakan Penanggulangan Demam Berdarah Dengue di Kota Sampang Jawa Timur - Habybil Mahbub (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2023)
Aides aegypti or Aides albopictus is a type of mosquito that carries and transmits dengue virus to humans. Dengue hemorrhagic fever appears as an Extraordinary Event (KLB), causing panic in the community because it has the risk of causing death and spreads very quickly. Based on records from the Directorate for Prevention and Control of Infectious Diseases (P2PM) until Week 36, the cumulative number of confirmed cases of DHF from January 2022 was reported as 87,501 cases (IR 31.38/100,000 population) and 816 deaths (CFR 0.93%). Sampang Regency, East Java, is currently starting to anticipate the possibility of an outbreak of dengue fever. After the local regency government released three districts that were considered prone to Dengue Hemorrhagic Fever (DHF), namely Sampang District, Omben District and Torjun District. The Health and Family Planning Service (Dinkes-KB) of Sampang Regency, East Java, noted that cases of dengue hemorrhagic fever (DHF) in the area have decreased in 2021 compared to the number of cases that occurred in previous years. This study aims to determine the implementation of dengue hemorrhagic fever (DHF) prevention policies in Sampang District and what are the inhibiting factors. In this study, researchers used a qualitative descriptive method that used data collection such as interviews, observation and documentation studies. Based on the research results in assessing the Implementation of Dengue Hemorrhagic Fever (DHF) Management Policies in Sampang Regency, it has not been maximized when viewed from several indicators of evaluating the implementation of public policies, namely (1) Policy resources such as a lack of health workers, sufficient health facilities and funds, (2) ) the disposition or attitude of the executors is not firm and the lack of community participation in PSN activities, (3) economic, social and political conditions that are not conducive.